2008
DOI: 10.1002/jso.21190
|View full text |Cite
|
Sign up to set email alerts
|

Patient and tumor factors at diagnosis in a multi‐ethnic primary head and neck squamous cell carcinoma cohort

Abstract: Background A long-term objective is to refine patient diagnosis and prognosis to address heterogeneity in head and neck squamous cell carcinoma (HNSCC) through incorporation of patient and tumor factors. This study examined histopathology and demographic variables at primary diagnosis (early vs. late stage) in a HNSCC patient population with a higher than usual percentage of African American (AA) subjects. Methods The primary HNSCC cohort was drawn from a diverse patient population and constructed through re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 27 publications
4
32
1
Order By: Relevance
“…In this LSCC cohort, with 41% AA patient representation, AA were more likely to have advanced stage disease than their CA counterparts, and this is consistent with previous HNSCC studies from our group (Sethi et al 2009). …”
Section: Discussionsupporting
confidence: 91%
“…In this LSCC cohort, with 41% AA patient representation, AA were more likely to have advanced stage disease than their CA counterparts, and this is consistent with previous HNSCC studies from our group (Sethi et al 2009). …”
Section: Discussionsupporting
confidence: 91%
“…The Settle et al 2009 16 study found that poorer survival outcomes for AA versus CA with oropharyngeal tumors were attributable to racial differences in the prevalence of HPV-positive tumors; HPV prevalence in AA was significantly lower than CA with similar survival outcomes for HPV-negative AA and CA patients. Our data on site concur with previously reported HNSCC diagnosis and prognosis outcomes from our group 25 .…”
Section: Discussionsupporting
confidence: 92%
“…HNSCC, often treated as a single entity, is in fact a heterogeneous group of tumors and outcome of both diagnosis and prognosis is strongly influenced by the anatomic site of the primary tumor 25,35 . In our study, among all HNSCC cohort patients, influence of location of the primary tumor on late stage diagnosis, with larynx as the reference site was the highest for cancer site as HP, followed by OP.…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective study cohort of 79 primary LSCC was examined for a set of 21 variables to include 8 histopathology factors 14 : tumor grade(well, moderate, poorly differentiated), lymphocytic response (continuous rim/ patchy infiltrate/ absent), desmoplastic response (prominent & diffuse/ patchy & irregular/ focal/ absent), pattern of invasion (host/tumor interface with pushing cohesive borders (mode 1)/ solid cords (mode 2)/ thin irregular cords(mode 3)/ single cells(mode 4)), vascular invasion (identified /absent), perineural invasion (identified /absent), reversed mitotic index (<5 mitosis per 10 high power fields (HPF)/ >5 mitosis per10 HPF) and necrosis (extensive/minimal/absent); demographics ( 5 variables-race [as self reported], gender, age, marital status and highest education), clinical factors (3 variables – comorbidity, pneumonia and family history of cancer), smoking, alcohol, stage, HPV status, and health insurance type. Overall comorbidity was determined using the Adult Comorbidity Evaluation 27 (ACE-27) index for cancer patients 15 .…”
Section: Methodsmentioning
confidence: 99%